Research progress in the detection of trace heavy metal ions in food samples - Si, Linxing; Wu, Qian; Jin, Yulong; Wang, Zhuo (Frontiers in Chemistry, 2024)
Food safety is the basis for ensuring human survival and development. The threat of heavy metal ions to food safety has become a social concern with the rapid growth of the economy and the accompanying environmental pollution. Some heavy metal ions are highly toxic even at trace levels and pose significant health risks to humans. Therefore, ultrasensitive detection of heavy metal ions in food samples is important. In this mini-review, recent advances in the analytical methods based on nanomaterials for detecting trace heavy metal ions in food samples are summarized in three categories: electrochemical, colorimetric, and fluorescent methods. We present the features and sensing mechanisms of these three methods, along with typical examples to illustrate their application in the detection of heavy metal ions in foods. This mini-review ends with a discussion of current challenges and future prospects of these approaches for sensing heavy metal ions. The review will help readers understand the principles of these methods, thereby promoting the development of new analytical methods for the detection of heavy metal ions in food samples.